Peran Politik dan Etika Pendidikan Dalam Proses Pembelajaran SDN Glagahwangi II - Sofia Fuadi; Sri Minarti (Advances In Education Journal, 2026)
This research discusses the relationship between politics and educational ethics and its implications in the learning process in schools. The purpose of this research is to analyze the role of education policy and ethical values in creating effective and quality learning. The research uses a qualitative approach with a type of library research which is strengthened through observation and simple interviews with teachers in schools. Data were obtained from journals, books, scientific articles, and interview results regarding the application of school ethics and policies in learning. The results of the study show that education politics is related to the policies and rules that govern the educational process, while educational ethics are a moral guideline in shaping the attitudes and behaviors of students. Student ethics have been proven to affect the quality of learning in the classroom. Teachers and school policies have an important role in instilling discipline and positive behavior. In conclusion, the balanced application of politics and educational ethics is very important to create an effective, fair, and conducive learning atmosphere.